2021
DOI: 10.3390/ma14144028
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healable Biocomposites Crosslinked with a Combination of Silica and Quercetin

Abstract: In this publication, novel bio-based composites made of epoxidized natural rubber with 50 mol% of epoxidation (ENR-50) are presented. The obtained materials, partially cured with a totally environmentally friendly crosslinking system consisting of natural ingredients, including quercetin and silica, exhibit a self-healing ability resulting from the self-adhesion of ENR-50 and reversible physical forces between the curing agent and the matrix. The impact of natural components on the crosslinking effect in uncur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Composites reinforced with fibers of organic origins also offer good strength, lightness, composite stiffness, low costs, a low friction coefficient, proper abrasive and erosive wear resistance, and, most importantly, biodegradability (including lower disposal costs) [25,26]; therefore, scientists are Materials 2023, 16, 6569 2 of 15 conducting more research into biocomposites. This is in line with increasing environmental awareness and the concepts of sustainable development (responsible waste management and designing products for recycling) [27][28][29]. Furthermore, this research complies with the circular economy strategy promoted by the European Commission and stipulates waste prevention and reuse [29].…”
Section: Introductionsupporting
confidence: 74%
“…Composites reinforced with fibers of organic origins also offer good strength, lightness, composite stiffness, low costs, a low friction coefficient, proper abrasive and erosive wear resistance, and, most importantly, biodegradability (including lower disposal costs) [25,26]; therefore, scientists are Materials 2023, 16, 6569 2 of 15 conducting more research into biocomposites. This is in line with increasing environmental awareness and the concepts of sustainable development (responsible waste management and designing products for recycling) [27][28][29]. Furthermore, this research complies with the circular economy strategy promoted by the European Commission and stipulates waste prevention and reuse [29].…”
Section: Introductionsupporting
confidence: 74%
“…It has been confirmed that this flavonoid exhibits a curing effect in polymer blends consisting of epoxidized natural rubber (ENR) and polycaprolacone (PCL) [ 17 ]. In our previous research, the crosslinking ability of quercetin was also confirmed in the ENR-50 matrix in the presence of silica [ 18 ]. This article is a continuation of the previous publication, which focused on the self-healing ability of ENR-50-composites.…”
Section: Introductionmentioning
confidence: 74%
“…Moreover, tannic acid was utilized as a crosslinker for catalyst-free silicone elastomers and to cure epoxidized soybean oil to obtain fully bio-based epoxy resin [ 23 ]. It was also proved that this acid is able to cure UV-treated epoxidized natural rubber to receive environmentally friendly films dedicated to coatings [ 24 ]. Tannic acid is definitely an interesting modifier, which can be utilized to obtain biomaterials demonstrating antiviral and antibacterial properties.…”
Section: Introductionmentioning
confidence: 99%